Investigation on wear and tool life of cutting tools - Kundrak, Janos; Raczkovi, L. (НТУ "ХПИ", 2011)
The wear of cutting tools is determinant in chip removal and tool life is in economic efficiency of cutting. The reason is that superhard tools are expensive and surfaces or parts machined by them have to fulfill strict requirements referring to the accuracy and quality. That is why investigation on these tools have a major importance. The paper focuses on some wear feature of CBN tools and on determining of tool life.

Износ режущего инструмента определяет отвод стружки и стойкость инструмента с точки зрения экономической эффективности резания. Причина в том, что сверхтвердые инструменты стоят дорого, а обработанные детали должны иметь строгие параметры в отношении точности и качества. Именно поэтому исследование этих инструментов имеет большое значение. Статья посвящена некоторым особенностям кубического нитрида бора и инструментов, влияющим на определение срока службы инструмента.
Исследование износостойкости режущих инструментов
Keywords: tool wear; wear intensity; superhard tools; срок службы инструмента; интенсивность износа